Study on removal of Se(IV) using Fe-Mn layered double hydroxides and Fe-Mn Dos (double oxides) - Otgonjargal, Enkhtur; Baek, Kitae; Yang, Jung-Seok; Surenjav, Enkhtuul; Khasbaatar, Aruukhan Dashkhuu (Mongolian Journal of Chemistry, 2019)
In this study, Fe-Mn-CO3 layered double hydroxide (LDHs) and Fe-Mn Double oxide (DOs) were synthesized by the co-recipitation methods for Se(IV) removal from aqueous solutions. The Se(IV) adsorption capacities and removal mechanism of Fe-Mn LDH and Fe-Mn DOs determined by batch and column experiments. The calculated Se(IV) adsorption capacities on Fe-Mn LDH and Fe-Mn DOs were 52.5 and 55.3 mg/g, respectively. Kinetic models applied to the adsorption of Se(IV) on the Fe-Mn LDH and Fe-Mn DOs calculated using pseudo-first, second-order, Elovich, and Intraparticle diffusion kinetic models and all kinetic parameters were calculated and discussed. Isotherm studies were also performed using Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich equations in the temperature range of 283 - 323 K. Adsorption kinetics and isotherm experiments are well fitted pseudo-second order model and Freundlich isotherm, respectively. The production of this adsorbent is cost-effective for industrial applications.